Are frail elderly people in Europe high-need subjects? First evidence from the SPRINTT data. Issue 8 (August 2020) - Sicsic, Jonathan; Ravesteijn, Bastian; Rapp, Thomas; ,
Highlights: Examine the association between physical frailty and care use in Europe. Compare the effect of frailty across five validated instruments. Frailty is significantly associated with increased emergency admissions, hospitalizations, and LTC use. Poor frail elders are more likely to use health care and LTC services. Support inclusion of frailty in the eligibility criteria of public LTC allowances. Abstract: Physical frailty and sarcopenia (PF&S) has received growing attention in empirical models of health care use. However, few articles focused on objective measures of PF&S to assess the extent of care consumption among the frail population at risk of dependency. Using baseline data from the SPRINTT study, a sample of 1518 elderly people aged 70+ recruited in eleven European countries, we analyse the association between various PF&S measures and health care / long term care (LTC) use. Multiple health care and LTC outcomes are modelled using linear probability models adjusted for a range of individual characteristics and country fixed effects. We find that PF&S is associated with a significant increase in emergency admissions and hospitalizations, especially among low-income elders. All PF&S measures are significantly associated with increased use of formal and informal LTC. There is a moderating effect of income on LTC use: poor frail elders are more likely to use any of the formal LTC services than rich frail elders. Our results are robust to various statistical specifications. They suggest that the inclusion of PF&S in the eligibility criteria of public LTC allowances could contribute to decrease the economic gradient in care use among the elderly community-dwelling European population.